ANALYSIS OF SHORT-CHAIN FATTY ACIDS AND ASSOCIATION WITH GLUCAGON-LIKE PEPTIDE-1 IN HEALTHY, OBESE, PREDIABETES AND TYPE 2 DIABETES INDIVIDUALS - Dede, S.; Karaku, E.; Yaman, M.; Bilen, O. (EDITURA ACAD ROMANE, 2025)
Context. Short-chain fatty acids (SCFAs) play a critical role in host metabolism, both directly and through specific G protein-coupled receptors, and may provide a link between glucose and lipid metabolism. This study aimed to compare fecal SCFA concentrations and to evaluate associations between SCFAs and glucagon-like peptide 1 (GLP-1) in individuals with type 2 diabetes (T2DM), prediabetes, obesity, and health. Subjects and Methods. The study included 60 volunteers in four groups: T2DM (n= 15), prediabetes (n= 15), obesity (n= 15), and healthy individuals (n= 15). We analyzed fecal SCFA and GLP-1 concentrations by HPLC-UV and ELISA method, respectively. Results. In comparison to healthy individuals, obese, prediabetic and T2DM exhibited notably elevated total SCFA levels respectively (p=0.019, p=0.017, p=0.024). Acetic acid concentration showed an increase in both obese andprediabetic groups compared to the healthy group (p=0.02, p=0.017). Butyric acid concentration was elevated in T2DM and prediabetic groups in comparison to both healthy and obese groups (p=0.024, p=0.017, p=0.07, p=0.56). The GLP-1 levels significantly decreased in the obese and prediabetic groups compared to the healthy and T2DM groups (p=0.00, p=0.021, p=0.000, p=0.005). GLP-1 was correlated with acetic acid, butyric acid, and the total SCFA concentrations in the T2DM and obese groups (r= 0.479, p= 0.098; r= 0.441, p= 0.099; r= 0.654, p= 0.015, respectively) while there was no correlation in the prediabetic group. Conclusion. Our results extend the knowledge on the alteration of SCFA levels in the states of obesity, prediabetes, and T2DM and enrich the understanding of the relationship between SCFAs and GLP-1.
Keywords: fecal short-chain fatty acids; glucagonlike peptide 1; type 2 diabetes; prediabetes; obesity; microbiota; GUT BACTERIA; SECRETION; GLP-1; Endocrinology & Metabolism